Система сбора и обработки полетной информации - Skubilin, M. D.; Pismenov, A. V.; Golovin, S. G.; Bubley, S. E. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
To ensure the unconditional availability of flight information at ground air traffic control centers, a subsystem for flight information backup is proposed. This subsystem can be seamlessly integrated into the existing flight information monitoring complex and is intended for real-time assessment (without relying on onboard recorders) of the technical condition of the aircraft and for analyzing the flight situation both during and after the flight.